The Effect of Giving Boiled Red Betel Leaf Water on Leucorrhea in Adolescent Girls of Grade XII at SMA Negeri 1 Sangkulirang - Desy Afriani Sysca; Tuti Meihartati; Widya Astutik; Chandra Sulistyorini (Green Publisher Indonesia, 2025)
Adolescent girls frequently experience leucorrhea, which can be either normal or pathological. According to WHO (2024), trichomoniasis is one of the primary causes of pathological leucorrhea, and over 1 million instances of curable STIs affect women between the ages of 15 and 49 every day. This study aimed to analyze the effect of giving red betel leaf decoction on the incidence of vaginal discharge in adolescent girls in grade XII at SMA Negeri 1 Sangkulirang. Method: This study used a quasi-experimental without a control design. The sample consisted of 30 female students who experienced vaginal discharge, selected using consecutive sampling techniques. The intervention was carried out by administering 70 ml of red betel leaf decoction twice a day for seven days. Measurements were taken before and after the intervention using questionnaires and observation sheets. This showed a significant decrease in the severity of vaginal discharge after the intervention. The Wilcoxon Signed Rank Test showed a p-value <0.001, which showed a significant difference before and after giving red betel leaf decoction. The Mean Ranks and Z-score values also showed a significant decrease. This indicates that red betel leaf decoction is effective in reducing vaginal discharge in female adolescents. Therefore, this method can be an alternative natural treatment that is safe and easy to apply. It is expected that the results of this study can provide benefits for young women in maintaining their reproductive health.